The roles and signalling pathways of lncMALAT1 in coronary artery disease: A protocol for systematic review of in vivo and in vitro studies - Jia Zheng; Arimi Fitri Mat Ludin; Nor Fadilah Rajab; Li Shaolong; Nurul Farhana Jufri (PLoS ONE, 2025)
Background Coronary artery disease (CAD) is a major cardiovascular disease that affects global population health. Several studies have indicated the association between high expression level of a non-coding RNA, lncMALAT1 and an increased risk of CAD. In this study, we conducted a protocol of systematic review aims to evaluate the role and mechanism of lncMALAT1 that may contributed to CAD based on animal and in vitro studies. The roles of lncMALAT1 will be elucidated focusing on activating upstream signalling Klotho/FGF23 or regulate the downstream Wnt/β-catenin or extracellular signal-regulated kinase/mitogen-activated protein kinase(ERK/MAPK) and any other pathways with the vascular changes in term of proliferation, migration, lumen formation and apoptosis. Methods A systematic review protocol with a reproducible strategy according to the Preferred Reporting Items for Systematic Review and Meta-analysis Protocols (PRISMA-P) guidelines and Population, Intervention, Comparison Outcome and Study (PICOS) framework were proposed to evaluate the existing literature on the roles and mechanisms of the lncMALAT1. A PRISMA-compliant electrical systematic research was performed in the databases including PubMed, Web of Science and Scopus for English publication from their inceptions until January 2024. Data for collection will include primary CAD animal models and any cardiomyocyte cell line with primary hypoxia model. The article title, authors, type of models, signaling pathways and biological changes (proliferation, migration, lumen formation and apoptosis) will be recorded. Conclusion This will provide a new approach in understanding molecular interactions on CAD for new perspective and target treatment for CAD patients in future, especially that intolerance of invasive coronary therapy. Registration Registered in PROSPERO on 10 April, 2024. (CRD42024504245) (https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024504245).